2017
DOI: 10.1039/c6cp05983j
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and diffusion of lithium in a graphene/blue-phosphorus heterostructure and the effect of an external electric field

Abstract: The adsorption and diffusion behaviors of lithium (Li) in a graphene/blue-phosphorus (G/BP) heterostructure have been investigated using a first principles method based on density functional theory (DFT). The effect of an external electric field on the adsorption and diffusion behaviors has also been investigated. The results show that the adsorption energy of Li on the graphene side of the G/BP heterostructure is higher than that on monolayer graphene, and Li adsorption on the BP side of the G/BP/Li system is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 57 publications
1
24
1
Order By: Relevance
“…21 The blue phosphorene is expected to be equally stable as BP but have a higher mobility, which is beneficial to FET application. 18,20,22,23 It has been demonstrated that blue phosphorene can be used as an anode material for Li-ion batteries, 24,25 thermoelectric materials, 26 and superconductor materials. 27 However, there has been no experimental research report on blue phosphorene FETs.…”
Section: Introductionmentioning
confidence: 99%
“…21 The blue phosphorene is expected to be equally stable as BP but have a higher mobility, which is beneficial to FET application. 18,20,22,23 It has been demonstrated that blue phosphorene can be used as an anode material for Li-ion batteries, 24,25 thermoelectric materials, 26 and superconductor materials. 27 However, there has been no experimental research report on blue phosphorene FETs.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive theoretical efforts have been made to explore the fundamental properties of blue phosphorus, including carrier mobility [31], electronic transport properties [32], thermal conductivity [33], and superconductivity [34]. The effects of atom doping [35], ion adsorption and intercalation [36,37], electric field [38], and strain [39] on the electronic and magnetic properties of blue phosphorus were addressed. The oxidized, hydrogenated, and fluorinated forms of blue phosphorus were also predicted [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…All the calculations have been carried out by using SIESTA code by the rst-principles [32,33]. Within SIESTA code, the generalized gradient approximation (GGA) with the Perdew-Burke-Ernzerhof functional (PBE) is widely applied to describe the electron exchange correlation term [34,35]. Meanwhile, the accuracy of the computed adsorption energies has been improved by the double-basis set [36].…”
Section: Methodsmentioning
confidence: 99%